Long-term Consequences, Chances of Re-infection, and Outcomes among Cases Recovered with Severe COVID-19 at a Tertiary Care Centre in Central India - Saad, Talha; Mishra, Satyendra; Rai, Hindeshwari; Rawat, Sumit Kumar (Institute of Topical Disease Universitas Airlangga, 2022)
COVID-19 has a wide disease spectrum. Different presentations may be seen in different people, with uncertain long-term fate. The amount and longevity of immunity provided among the infected also vary from person to person which might in turn affect the chances of re-infection. Current study tries to uncover the incidence, disease severity and outcomes amongst those who have been previously hospitalized for COVID-19. A prospective cohort study where all patients admitted to intensive care facility at the tertiary care center were followed up for any occurrences of re-infection for more than one year. All cases were followed up telephonically and at scheduled visits to the hospital by trained personnel. A total of 410 cases with a mean age of 59.8 years, including 310 (75.6%) males and 100 (24.4%) females. Among these 410 patients 287 remained alive till the end of study period. Re-infection rates among recovered ICU admitted seriously ill patients were 1.4% whereas the rate of ICU re-admission due to COVID-19 re-infection was only 0.7%. Re-infection among female was 1.1% whereas in male was 1.5%. ICU readmission rate among female was 1.1% while in male was 0.5% only. The chances of re-infection in female were seen less than that in males, but the severity of re-infection in females was found to be higher. COVID-19 re-infection in previously severely infected COVID-19 patient is not so common. The chances of a severe disease among such cases are even rarer.